The Video supported collaborative learning knowledge alliance Erasmus+ (EU)-project. - Ramos, José Luis (2020)
YouTube, Vlogging, SnapChat, Skype, smartphones and video in WhatsApp etc. is what youth and adults use in their daily and working life to communicate. We are visual thinkers, observational learners and thus social learners (Bruner, 1961), so using visuals in education has many benefits. However, most teachers do not know how to use videos systematically in teaching (OECD, 2017). Europe-wide, there is a need for competent teachers in utilizing e-learning with leading digital collaboration solutions. The same holds true for pedagogical knowledge of designers in educational technology companies. The potential of video-supported learning has not been opened in teacher education (Hobbs, 2006). Education and companies alike lack pedagogical models and structures to promote learning from and with videos (Krauskopf, Zahn, Hesse, & Pea, 2014) Video-based e-learning in particular is one of the most emphasized 21st century teaching-and-learning approaches. Showing a video is not enough (Van Gog, Verveer, & Verveer, 2014). However, most teachers do not use video tools in a way that contributes to developing conceptual thinking and problem solving skills as relevant work-life competences of the knowledge worker (Bereiter, 2002). The modernization of European Higher Education Institutes (HEIs) calls for a workable pedagogy and skilled teachers to take on the up-to-date video-supported collaboration solutions for creative teamwork in online environments. In this contribution we want to explain the ViSuAl-project, which tries to address the previous challenges. In particular, after introducing the project and its reference framework, we will present the first ViSuAl milestone: a state of the art review on video use and collaborative learning.